Different thermal treatments of highland barley kernel affect its flour physicochemical properties by structural modification of starch and protein. (1st September 2022) - Wang, Haoran; Li, Zaigui; Wang, Lili; Cui, Steve W.; Qiu, Ju
Graphical abstract: Highlights: Thermal treatments changed starch arrangement and protein secondary structure. Superheated steam led to tightest starch granules aggregation embedded in protein. Superheated steam at 180 °C decreased the damaged starch level. Superheated steam at 180 °C delayed starch retrogradation. Superheated steam at 180 °C decreased the elasticity and viscosity of gel. Abstract: Highland barley (HB) has become popular due to nutritional benefits, and thermal treatment could broaden its application. In this study, superheated steam (SS) as a novel commercially thermal treatment was compared with other traditional heating (steam and roasting). The physiochemical properties of treated HB kernels and subsequent produced flour were investigated. After thermal treatments, gelatinization enthalpy was decreased by 38.39% and the degree of gelatinization was increased by 38.40%. SS at 180 °C (SS-180) induced the highest thermal stability, lowest viscoelasticity gel and delayed the starch retrogradation compared to other treatments. Meanwhile, SS-180 caused lowest short-range order and relative crystallinity of starch along with changes in protein secondary structure. Particularly, SS-180 decreased damaged starch content by 6.44% due to starch granules closely wrapped by glue-like protein, while steam and roasting increased it by 32.92% and 21.40%, respectively. Overall, SS treatment is most effective to improve the physiochemical properties of HB.